The role of inter-specific competition for water in maize-legume intercropping systems in northern Tanzania - Mugi-Ngenga, E.; Bastiaans, L.; Anten, N.P.R.; Zingore, S.; Baijukya, F.; Giller, Kenneth E. (Elsevier, 2023)
CONTEXT Maize-legume intercropping is common in sub-Saharan Africa. Effects of legumes on the companion maize crop are determined principally by choice of legume species and relative introduction time. Performance of intercrops is optimized when legumes' planting is timed such that their peak growth phase occurs after maize harvest, with legumes utilizing the residual soil moisture.